Heavy elements accumulation in dominants aquatic plants at Al-Chibayish Marshes, South of Iraq - Al-Atbee, Rehab S.K.; Al-Hejuje, Makia M.; Al-Saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2019)
The present study concerned with the heavy elements (Cd, Cr, Ni and Pb) concentration that accumulated in dominant species of aquatic plants (submerged; Ceratophyllum demersum) and (merged; Phragmites australis, Typha domingensis and Schoenoplectus littoralis), in relation to the concentration of these elements in each of the dissolved phase of water and sediments samples which collected seasonally from four sites at Al-Chibayish marshes during August 2017 to April 2018. Also Bioaccumulation factor (BAF) was calculated. The results showed that the highest concentrations of heavy elements was in the sediments, then the aquatic plants and the lowest concentrations was recorded in dissolved phase, whereas the Bioaccumulation Factor (BAF) of heavy elements in aquatic plants, shows that Ceratophyllum demersum have the highest concentration than the other species.